Observations of highly oxygenated organic molecules in the high Arctic - Lehmusjärvi, Tuuli (Helsingin yliopisto, 2022)
The effects of atmospheric aerosol particles on Earth’s radiative balance are mainly cooling, which is mostly due their indirect effects with clouds. In the Arctic more than half of the cloud condensation nuclei (CCN) production is originated from secondary aerosols, and to further the understanding of Arctic climate and its changes due to the global warming, it is necessary to better understand the secondary aerosol processes there. Highly oxygenated organic molecules (HOM) are known to be important for the formation and especially for the growth of newly formed secondary aerosols to climate relevant sizes. Because of the low volatilities of HOM, they can condense onto the smallest particles, which is crucial for the growth of the new particles. Volatile organic compounds (VOC), especially monoterpenes, are known to be sources of HOM in boreal forest, but in the Arctic where the vegetation is scarce the sources of HOM have not yet been identified. The processes related to secondary aerosol formation in the Arctic are still not fully understood. Especially the observations of HOM and their sources are lacking. Recent studies in Ny-Ålesund, Svalbard showed that multiple aerosol precursors are found to be present in the Arctic atmosphere, as well as contributing to the early stages of the formation of secondary particles. However, more molecular scale observations of aerosol precursors are still needed to form a full picture of the Arctic climate processes. In this thesis, the different aerosol precursors and their contributions to the new particle formations in high Arctic location Ny-Ålesund, Svalbard were analysed. Chemical compositions of HOM were identified for the first time from Arctic atmosphere, and their contributions to new particle formation in high Arctic location were investigated. Because of the high concentrations of HOM during the observed NPF events, it can be suggested that they were contributing to the nucleation of aerosol particles. Particle growth rate calculation shows that the HOM present ...